2013
DOI: 10.4236/ajps.2013.411260
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Economic Assessment of Wheat under Tillage and Nitrogen Levels in Rice-Wheat System

Abstract: Mechanically post-harvest puddled rice field has stubbles that often delay timely planting of winter wheat crop. Zero tillage increased the net return by decreasing the unwise tillage operations and labor charges. Keep in view, a randomized complete block design experiment in a split plot arrangement was conducted with four tillage system [conventional tillage, CT; deep tillage, DT; zero tillage with zone disc tiller, ZDT; and happy seeder, HS] in main plots and five nitrogen levels [0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In a comprehensive review of studies examining the influence of tillage practices on wheat by Kaur et al [11] observed that plant height varied notably, with the highest heights recorded in conventional tillage with mulch (108.4 cm), followed by zero tillage with mulch (101.8 cm), and the lowest heights in conventional tillage without mulch (95.5 cm). These findings underscore the importance of soil physical conditions and moisture conservation in shaping plant growth dynamics, in line with previous research by Qamar et al [12]. Expanding on this theme, Goswami et al [13] delved into the effects of irrigation and tillage on plant height, revealing that conventional tillage resulted in the greatest plant height at 120 days after sowing, which was 11 times greater than minimum tillage, attributed to improved soil structure conducive to root establishment and moisture retention.…”
Section: Role Of Mechanization In Rice Wheat Cropping Systemsupporting
confidence: 92%
“…In a comprehensive review of studies examining the influence of tillage practices on wheat by Kaur et al [11] observed that plant height varied notably, with the highest heights recorded in conventional tillage with mulch (108.4 cm), followed by zero tillage with mulch (101.8 cm), and the lowest heights in conventional tillage without mulch (95.5 cm). These findings underscore the importance of soil physical conditions and moisture conservation in shaping plant growth dynamics, in line with previous research by Qamar et al [12]. Expanding on this theme, Goswami et al [13] delved into the effects of irrigation and tillage on plant height, revealing that conventional tillage resulted in the greatest plant height at 120 days after sowing, which was 11 times greater than minimum tillage, attributed to improved soil structure conducive to root establishment and moisture retention.…”
Section: Role Of Mechanization In Rice Wheat Cropping Systemsupporting
confidence: 92%
“…Conventional tillage consistently to more proliferation of roots because of less bulk density(Singh and Singh 2021). Similar results have also been reported by(Qamar et al 2013 andXu et al 2018). Kalaydjieva et al (2015) reducing the irrigation rates display a negative impact on the values of LAI.…”
supporting
confidence: 79%
“…Irrespective of tillage and residue management practices, maximum LAI was observed under I2 (4.60) followed by I1 (3.95) and least under I3 (3.70). Qamar et al(2013) also observed maximum LAI of wheat under DT followed by NTR and minimum under CT. The data related to the effect of tillage -residue practices and irrigation regimes on relative leaf water content (RLWC) is presented in Table 1.Effect of tillage-residue management practices was found to be non significant whereas irrigation effect on RLWC was significant.…”
Section: Resultsmentioning
confidence: 86%